Diagnosis of mypes from the Colombian technical standard (ntc) 6001:2017 - Vásquez López, Lenys Esther (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The research makes a diagnosis of 17 micro and small companies (Mypes) affiliated with the Association of Micro and Small Entrepreneurs of Montería, Colombia, applying a survey to evaluate the development of the processes in compliance with the Colombian Technical Standard 6001: 2017. The results of the analysis of variance show that they are more oriented towards short-term support processes, such as commercial management, neglecting the improvement of product development processes, medium and large growth, and knowledge of the environment, concluding that Mypes have weaknesses in the management of paperwork and paperwork.